2019
DOI: 10.15294/jdm.v10i2.19674
|View full text |Cite
|
Sign up to set email alerts
|

Motivation to Transfer Training and Individual Performance: the Influence of Transformative Learning and Supervisor Support

Abstract: This article discusses the mediating role of motivation to training transfer as mediation in the relationship between supervisor support and transformative learning on lecturer performance. Survey methods and purposive non random sampling techniques were used with the help of a questionnaire based on a 7-point Likert scale. The number of fit samples was 199 to test the hypothesis. Amos and structural models are used to test the statistical significance of the path coefficients. The findings of the study explai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 34 publications
1
7
0
Order By: Relevance
“…The influence of transfer opportunity on assimilated training content is supported by Baldwin and Ford (1988) and Tannenbaum and Yukl (1992). The findings of Pudjiarti et al (2019) and Islam (2019) also support the discovery made relative to the influence assimilated training content has on motivation to transfer. Similarly, the revelation regarding assimilated training content and training transfer in this study is similar to those by Nafukho et al (2017), Ali et al (2022) and Dewayani and Ferdinand (2019).…”
Section: Discussionsupporting
confidence: 60%
See 2 more Smart Citations
“…The influence of transfer opportunity on assimilated training content is supported by Baldwin and Ford (1988) and Tannenbaum and Yukl (1992). The findings of Pudjiarti et al (2019) and Islam (2019) also support the discovery made relative to the influence assimilated training content has on motivation to transfer. Similarly, the revelation regarding assimilated training content and training transfer in this study is similar to those by Nafukho et al (2017), Ali et al (2022) and Dewayani and Ferdinand (2019).…”
Section: Discussionsupporting
confidence: 60%
“…The influence of transfer opportunity on assimilated training content is supported by Baldwin and Ford (1988) and Tannenbaum and Yukl (1992). The findings of Pudjiarti et al (2019) and Islam (2019) More so, the mediating role of motivation to transfer in the training transfer process is established in the studies of Paulsen and Kauffeld (2017), Reinhold et al (2018), Richter and Kauffeld (2020), Seiberling and Kauffeld (2017) and Bhatti et al (2014).…”
Section: Structural Modelmentioning
confidence: 81%
See 1 more Smart Citation
“…In addition, the positive impact of transfer training and other organizational outcomes can also improve employee positions. Supported by several studies that are in line (Martins et al, 2019;Obaid et al, 2016;Pudjiarti et al, 2019) improve the transfer of training by encouraging employees to share their knowledge with other employees after attending the training. This can improve the work performance of employees, one of which is due to the success of the transfer of training.…”
Section: Discussionmentioning
confidence: 97%
“…In previous studies regarding the transfer of training to work performance or organizational commitment, it was found that the transfer of training had a significant positive effect on work performance and organizational commitment. (Casey et al, 2021;Gautam & Basnet, 2020;Martins et al, 2019;Mozammel, 2019;Obaid et al, 2016;Otoo et al, 2019;Pudjiarti et al, 2019;Shaheen & Soomro, 2022). Transfer of training is measured using 6 indicator items from Turab & Casimir, (2015)…”
Section: Training Transfermentioning
confidence: 99%